The distance variation due to mass transfer and mass loss in (13.6+8) Mand (13+10) M binary star systems - Abdulameer, Mohammed R. (Iraqi Journal of Physics, 2019)
In this research the change in the distance of the two stars in two binary star systems (13.6+8)M8and (13+10)M8 was studied, through the calculations the value (rate of mass transfer) of the two phases of dynamical stages of mass which are mass loss and mass transfer has been extracted in its own way ,by extracting the value of the value of (the distance variation between the two stars) has been found only in the mass transfer stage by using mathematical model ,in mass loss stage and were calculated from the change and the difference between the values of each at different times of binary star system evolution ,it was found that the maximum values of and are in mass transfer state in binary star system , in other words the maximum values of depend on the mass transfer between the two component stars of the binary star system.